Anacyphrethines A and B as potent analgesics: Multiple ion channel inhibitors with an unprecedented chemical architecture - Hui Chen; Hanqi Zhang; Chao Niu; Bianlin Wang; Biao Gao; Zhijun Liu; Guangmin Yao; Haji Akber Aisa (Acta Pharmaceutica Sinica B, 2025)
Multi-target analgesics with minimal side effects and high efficacy are a key research focus in addressing the global pain crisis. Using a molecular networking approach, five pairs of potent analgesic alkaloid enantiomers were isolated from the roots of Anacyclus pyrethrum (A. pyrethrum). Their structures were elucidated by comprehensive spectroscopic data analysis, including LR-HSQMBC and 1H–15N HMBC, quantum 13C NMR DP4+ and ECD calculations, and single-crystal X-ray diffraction analysis. Anacyphrethines A (1) and B (2) are highly conjugated and polymethylated 6/6/6/6/5/7/5/5-fused octacyclic tetraazabic alkaloids possessing an unprecedented 8,14,18,24-tetraaza-octacyclo[16.8.2.11,23.04,28.05,17.09,16.011,15.021,27] nonacosane motif. Their biosynthetic pathways are proposed involving key aldol, hydroamination, and Schiff base reactions. All isolates showed potent analgesic effects in vivo. Even at a lower dose of 0.2 mg/kg, (±)-1 and (+)-1 still exhibited more potent analgesic activities than morphine. Interestingly, the racemic mixture (±)-1 showed stronger analgesic effect than either pure enantiomer alone at higher doses of 5 and 1 mg/kg; while, (±)-1 showed significant analgesic activities comparable to (+)-1 at lower doses of 0.2 and 0.04 mg/kg. (+)-1 had stronger analgesic effect than (−)-1 at five tested does. Further tests on 44 analgesic-related targets demonstrated that (+)-1 showed significant inhibitory effects against many ion channels such as TRPM8, Kv1.2, Kv1.3, and Cav2.1 with IC50 values of 1.10 ± 0.26, 4.20 ± 0.07, 2.20 ± 0.24, and 10.40 ± 0.69 μmol/L, respectively, while (−)-1 primarily inhibited TRPC6, Kv1.2, and Kv1.3 ion channels with IC50 values of 0.81 ± 0.05, 0.91 ± 0.04, and 1.50 ± 0.13 μmol/L, respectively, without affecting the opioid receptors, suggesting their non-opioid analgesic potentials. The molecular dockings provided structural guidance to develop potent non-opioid analgesics.